Lessons Learned and Future Actions: Modifying a Stroke Specific Self-Management Program - Hreha, Kimberly; Sonnenfeld, Mandi; Na, Annalisa; Kitchens, Riqiea; Reistetter, Timothy A. (Frontiers in Health Services, 2022)
Background: Self-management programs have been shown to be effective at providing support to individuals who want to manage chronic health conditions independently. It has been shown that adapting self-management programs for different diagnostic groups, such as stroke, is essential. Objective: To report modifications made during trial implementation, the barriers identified during the delivery of an evidence based, stroke-specific self-management program and minor data from a small cohort of stroke survivors with multiple chronic conditions. Methods: Prospective type III hybrid implementation-effectiveness trial for individuals living in the community and interested in self-management. Modifications were reported: (1) researcher reflections (2) barriers and (3) strategies used to address the barrier using the Consolidated Framework for Implementation Research (CFIR) guidelines from field notes. Results: Twenty-five individuals consented (42% of eligible sample) at the time of acute stroke and five were interested in continuing at the 3-month call. Multiple barriers to implementation were identified, resulting in modifications. For example, before the group sessions began, the COVID-19 pandemic necessitated changes to the intervention delivery. The protocol was modified to an online mode of delivery. In total, seven modifications were made. Conclusions: The CFIR was a facilitative tool to report barriers and strategies and emphasized the importance of comprehensive reporting. The modifications to the study were an essential first step to address the research climate and needs of this stroke cohort. Next steps include continued research with a larger cohort to implement effective strategies and answer the clinical question of effectiveness of the adapted and modified intervention.